Total ozone variability and trends over the South Pole during the wintertime - Fioletov, Vitali; Zhao, Xiaoyi; Abboud, Ihab; Brohart, Michael; Ogyu, Akira; Sit, Reno; Lee, Sum Chi; Petropavlovskikh, Irina; Miyagawa, Koji; Johnson, Bryan J.; Cullis, Patrick; Booth, John; et al. (Atmospheric Chemistry and Physics, 2023)
The Antarctic polar vortex creates unique chemical and dynamical conditions when the stratospheric air over Antarctica is isolated from the rest of the stratosphere. As a result, stratospheric ozone within the vortex remains largely unchanged for a 5-month period from April until late August when the sunrise and extremely cold temperatures create favorable conditions for rapid ozone loss. Such prolonged stable conditions within the vortex make it possible to estimate the total ozone levels there from sparse wintertime ozone observations at the South Pole. The available records of focused Moon (FM) observations by Dobson and Brewer spectrophotometers at the Amundsen–Scott South Pole Station (for the periods 1964–2022 and 2008–2022, respectively) as well as integrated ozonesonde profiles (1986–2022) and MERRA-2 reanalysis data (1980–2022) were used to estimate the total ozone variability and long-term changes over the South Pole. Comparisons with MERRA-2 reanalysis data for the period 1980–2022 demonstrated that the uncertainties of Dobson and Brewer daily mean FM values are about 2.5 %–4 %. Wintertime (April–August) MERRA-2 data have a bias with Dobson data of −8.5 % in 1980–2004 and 1.5 % in 2005–2022. The mean difference between wintertime Dobson and Brewer data in 2008–2022 was about 1.6 %; however, this difference can be largely explained by various systematic errors in Brewer data. The wintertime ozone values over the South Pole during the last 20 years were about 12 % below the pre-1980s level; i.e., the decline there was nearly twice as large as that over southern midlatitudes. It is probably the largest long-term ozone decline aside from the springtime Antarctic ozone depletion. While wintertime ozone decline over the pole has hardly any impact on the environment, it can be used as an indicator to diagnose the state of the ozone layer, particularly because it requires data from only one station. Dobson and ozonesonde data after 2001 show a small positive, but not statistically significant, trend in ozone ...